Epidemic of medical errors and hospital-acquired infections : systemic and social causes - Charney, William, 1947- (Boca Raton, Fla. : CRC Press, 2012)
"'Do no harm' a particularly leading and important phrase in the delivery of healthcare is not working. In fact depending on the epidemiological approach and which data sets one applies, medical errors, hospital acquired infections (HAIs) and pharmaceutical errors combined are the second or third leading killer of Americans annually: approximately 300,000 die from a combination of medical errors, hospital acquired infections (HAIs), and pharmaceutical errors ... 100,000 per category. Add to these numbers the hundreds of thousands who are harmed (morbidity) but not killed (mortality) changing quality of life and a substantial problem is defined"--Provided by publisher.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Medical errors -- Prevention -- United States; Cross infection -- Prevention -- United States; Medical care -- United States; Electronic books